Analisa Penerapan Entrepreneurial Marketing Syaria dan Dampaknya Terhadap Kinerja Usaha (Studi Pada Pelaku Usaha UMKM Kerajinan Keramik di Banjarnegara) - Aulia, Nafisa Farkhiy; Dirgantara, I Made Bayu (ITB AAS INDONESIA Surakarta, 2023)
This study aims to analyze the application of entrepreneurial marketing and its impact on business performance (Study on Micro, Small and Medium Enterprises Entrepreneurs in Banjarnegara). The qualitative method uses the question model